Rancangan Feeder Circlip untuk Meningkatkan Produktivitas Proses Machining pada Line Swing Arm di PT. Astra Otoparts Tbk. Divisi Nusametal - Robbi Malik; Kris Witono (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
In manufacturing industries, machining processes play a critical role in ensuring product quality, precision, and production efficiency. However, in the production of swing arm parts, the machining process has been identified as a bottleneck due to its non-optimal cycle time. One of the main issues contributing to this inefficiency is the disorganized handling of circlip inner parts. These components are often scattered without a designated placement system, which creates significant difficulties for operators when retrieving and installing circlips onto the swing arm. Such abnormalities disrupt workflow continuity, extend production time, and reduce overall productivity. To address this challenge, a circlip feeder machine was designed as a supporting device to assist operators and streamline the machining process. The design emphasizes efficiency, integration, and systematic operation by utilizing readily available workshop materials. The developed feeder machine is equipped with a robust frame construction and has a storage dimension capable of accommodating up to 200 circlips. In addition, mechanical analysis demonstrates that the feeder structure can withstand a maximum applied force of 31,475 N, ensuring durability and reliability during operation. The introduction of this circlip feeder machine directly impacts the production process by reducing operator workload, minimizing delays caused by disorganized parts, and ensuring faster and more accurate installation of circlips. Consequently, the overall machining cycle time is shortened, thereby improving production flow and enhancing the efficiency of swing arm part manufacturing. Beyond immediate time savings, the use of the feeder machine contributes to better resource utilization, reduced ergonomic strain on operators, and improved consistency in product quality. This study highlights the significance of simple yet effective mechanical innovations in overcoming production bottlenecks and optimizing manufacturing processes in automotive component industries.